Legitimating negative behaviors in companies: Why the buck doesn't stop with the leader. Issue 4 (4th July 2021) - Toader, Andra F.; Kunze, Florian
ABSTRACT: Negative leadership may have drastic consequences for organizations and society. However, leaders do not operate independently but supervise followers who potentially perpetuate their negative . Currently, we lack an integrated understanding of those followers who are more likely to model negative leader . There are two perspectives on why people model negative leaders: (a) because they are endowed with role-model powers through their authority and legitimacy; (b) because they are prototypical of the group. We propose that both perspectives are limited and introduce an integrative model which proposes that: To be modelled, negative leaders need to be prototypical of their groups and demonstrate the negative behaviours others can model. We test this model in four studies across various research designs, samples, and behavioural outcomes. We find consistent evidence that followers will model only prototypical ingroup leaders, but not outgroup leaders, who demonstrate negative behaviours and tie them with desirable outcomes. This model represents a significant step towards understanding the intricate relationships between negative leaders and their followers. We encourage future research to develop and test alternative models of negative behaviour modelling.